2022
DOI: 10.14306/renhyd.26.3.1693
|View full text |Cite
|
Sign up to set email alerts
|

Uso de suplementos nutricionales y productos a base de extractos de plantas en población española: un estudio transversal.

Abstract: Introducción: el mercado de suplementos registra grandes ventas, pero los datos de prevalencia y razones de uso en España son escasos. Los objetivos del estudio fueron evaluar la prevalencia de uso de suplementos, así como identificar por qué, para qué, modo de uso, quién los prescribe y dónde se adquieren. Metodología: estudio transversal mediante cuestionario ad-hoc autoadministrado online a 2.630 participantes (50% mujeres) de características sociodemográficas asimiladas a la población española. Encuesta de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Recently, the Spanish Association of Nutrition and Dietetics published a study conducted in 2630 adults with the aim of assessing the prevalence of nutritional supplementation in the Spanish population. A total of 40% of the respondents reported vitamin supplementation and 31% specifically vitamin C supplementation [ 34 ]. Intake was significantly higher in women, younger people (26–35 years), those with higher education, and the physically active [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Spanish Association of Nutrition and Dietetics published a study conducted in 2630 adults with the aim of assessing the prevalence of nutritional supplementation in the Spanish population. A total of 40% of the respondents reported vitamin supplementation and 31% specifically vitamin C supplementation [ 34 ]. Intake was significantly higher in women, younger people (26–35 years), those with higher education, and the physically active [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 40% of the respondents reported vitamin supplementation and 31% specifically vitamin C supplementation [ 34 ]. Intake was significantly higher in women, younger people (26–35 years), those with higher education, and the physically active [ 34 ]. These demographic characteristics could explain the low percentage of vitamin C supplementation observed in our sample, which was mostly constituted of men (68.3%), those of advanced age (≥65 years) (56.4%), those with primary education (51.3%), and those who did not engage in regular physical activity (65.8%); therefore, our sample is not representative of the population that consumes vitamin C supplementation, which was expected.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, the micronutrient with the highest number of approved health claims was zinc (18 declarations), followed by vitamin C (15), magnesium (10), copper (8), calcium (8), and iron (7). On the contrary, manganese had the lowest number of authorized health claims (4).…”
Section: Health Claims Approved In the Eu For Analyzed Micronutrientsmentioning
confidence: 99%
“…In 2022, a survey conducted in 14 European Member States, including Spain, revealed that almost 9 in 10 European consumers had taken food supplements in their lives, and the great majority of them (93%) had done it in the past year [7]. Baladia et al (2021) performed a comprehensive market study on the consumption of these products by the Spanish population (18-65 years), and the results demonstrated that 70% of the studied Spanish sample (N = 2630) took at least one food supplement during a specific period in 2020, with the most used (63%) being the ones containing vitamins and minerals. Vitamin C (31%) and magnesium, calcium, iron, zinc, and copper (6-13%) are the most frequently present vitamins and minerals in these food supplements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some consumers even believe that these supplements are useful to make up for nutritional deficits resulting from incorrect dietary habits [ 1 , 2 , 3 ]. Dietary supplements are known for providing different nutrients to supplement the diet, and they are usually consumed with the aim of increasing muscle mass, improving physical performance, replenishing nutrients or energy, and maintaining an adequate state of health [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%